The role, place and significance of event-management in the present conditions - Klimova, A. (ТДАТУ, 2018)
Our work has led us to the conclusion that the modern reality is characterized by an increase in the number of events and events in business and public life, increasing their social significance, so the value of event management in the efficiency of management is steadily increasing
Keywords: market economy; management; practical interest; Ukraine